Juan Felipe Herrera : migrant, activist, poet laureate - Lomelí, Francisco A.; Gómez, Osiris Aníbal (University of Arizona Press, 2023)
"This book is a wide-ranging collection of critical approaches on the highly accomplished poet Juan Felipe Herrera, who transcends ethnic and mainstream poetics. The chapters in this book expertly demonstrate the author's versatility, resourcefulness, innovations, and infinite creativity"--